Teaching practice as a modern exercise in our present - Rodríguez Centeno, Claudia Alejandra (Revista Ethika+, 2023)
We are faced with a reality endowed with great richness thanks to the diversity it presents, a reality that is not foreign to school institutions and that, at times, seems not to be understood and accepted by a part of societies considered postmodern. This article raises a reflection on the teaching performance that, beyond being a transmitter of knowledge, acts as a trainer of citizens. It is postulated that the school is a space where plurality coexists, revealing the lack of social equity and, therefore, educational inequality.